Prevention of Renal Complications Induced by Non- Steroidal Anti-Inflammatory Drugs - VuĦ#141;koviĦ#135, Sonja; SaviĦ#135; VujoviĦ#135, Katarina; Srebro, Dragana; MediĦ#135, Branislava; Ilic-Mostic, Tatjana (Current Medicinal Chemistry, 2016)
Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly prescribed for the treatment of pain, inflamation and fever. They are usually well tolerated in healthy persons, but in patients with risk factors (advanced age, renal impairment, heart failure, liver disease, concurrent medications with antihypertensive drugs), NSAIDs can induce serious renal adverse effects. They include sodium and water retention with edema, worsening of heart failure, hypertension, hyponatremia, hyperkalemia, acute kidney injury, chronic kidney disease, renal papillary necrosis and acute interstitial nephritis. The majority of these adverse effects are due to the inhibition of prostaglandins synthesis and they are dose and duration-dependent. Acute forms of kidney injuries are transient and often reversible upon drug withdrawal. Chronic use of NSAIDs in some patients may result in chronic kidney disease. It is recommended that patients at risk should have preventative strategies in place, including the use of the “lowest effective dose” of NSAID for the “shortest possible time” and monitoring renal function, fluid retention and electrolyte abnormalities. Patients who are taking antihypertensive medications should be monitored for high blood pressure and the doses of antihypertensive medications should be adjusted if needed. In general, the combination of NSAIDs and angiotensin inhibitors should be avoided. Some other preventive measures are dietary salt restriction, use of topical NSAIDs/non-pharmacological therapies and use of calcium channel blockers for treating hypertension.
Keywords: Non-steroidal anti-inflammatory drugs